Обгрунтування методики оцінювання стійкості функціонування фондового ринку України - Ячменьова, В.М.; Воробець, Т.І. (Культура народов Причерноморья, 2013)
У статті проаналізовано існуючі методики оцінки стійкості функціонування систем різних
рівнів. Проведено порівняння методик та визначено доцільність їх застосування для визначення стійкості
функціонування фондового ринку України. Визначено критерії, яким повинні відповідати методики оцінки
стійкості функціонування фондового ринку. В статье проанализированы существующие методики оценки устойчивости
функционирования систем различных уровней. Проведено сравнение методик и определена
целесообразность их применения для определения устойчивости функционирования фондового рынка
Украины. Определены критерии, которым должны соответствовать методики оценки устойчивости
функционирования фондового рынка. The existing methods of evaluation of stability of function of systems of different levels have been
analyzed in the article. Thus, the attention is paid to the works of N.Viner who first described and solved the
most important task on the search of the structure of optimized management system, that is the task of synthesis
of optimized system. In return, Kahlman offered the other view of solution of the task of construction of
optimized management system, different from N. Viner’s one. Such a presentation of solution in the form of a
closed loop system, similar in its kind to the forming filter, had large prospects of success. V.V.Novozhilov states
that the purpose of his modeling is the stability of technological system, calculating its reliability and safety. The
structure modeling and the graph theory are used as the tools. V.P. Bocharnikov suggests defining the stability
of judgments as for taking the management decision in market researches, using the theory of fuzzy measures,
Fuzzy-technology in Excel sphere. S.V. Glivenko suggests using the theory of fuzzy measures and integrals in
order to define the stable process of forecasting. A.V. Leonenkov, M.L. Krichevskiy and V.V. Borisova prefer the
Theories of fuzzy sets, the method of fuzzy logic for evaluation of uncertainty of stability in Mathlab sphere. The
performed comparison of methods defines the reasonability of their implementation in order to define the
stability of the stock market’s function in Ukraine. It also allows to give preference to fuzzy logic since this
mathematic theory has a number of advantages including the following: it allows to work out rapidly the
prototype of the system based on expert evaluation with further complication of its function; the model based on
fuzzy inference is more transparent (easier to understand) than the similar model based on differential or other
equations; fuzzy models are easier to operate by hardware, and at the same time it is possible to separate
calculations. The criteria to which the methods of evaluation of stability of the stock market’s function should
correspond are also defined, and the conclusions have been made.